Community Diagnosis Tentang Wabah Penyakit Demam Berdarah Dengue (DBD) di Dusun Kedungpoh Kidul, Nglipar, Gunungkidul - Suci Musvita Ayu; M. Reza; Khairunnisa Khairunnisa; Rizki Arum M.; Ryani Dwi Kurniati; Dana Kristiani; Dian Utami; Fanimas Tiwi; Cahyaningsih Cahyaningsih; Nida Alifah (Universitas Muhammadiyah Semarang, 2020)
Dengue Hemorrhagic Fever (DHF) is one of the diseases that is currently an environmental health problem. Cases are increasing and spreading more widely. This is coupled with the movement of mobility and population density in an area. The method used is a quantitative descriptive research study to get an overview and information about health conditions related to Dengue Fever. The results obtained are the high rate of spread of DHF in the rainy season. The conclusion of the prevalence of existing health problems is the magnitude of the DHF distribution rate of 25%.